Ferroptosis: a new unexpected chance to treat metastatic melanoma?. Issue 19 (1st October 2020) - Gagliardi, Mara; Saverio, Valentina; Monzani, Romina; Ferrari, Eleonora; Piacentini, Mauro; Corazzari, Marco
ABSTRACT: Human skin melanoma is one of the most aggressive and difficult to treat human malignancies, with an increasing incidence over the years. While the resection of the early diagnosed primary tumor remains the best clinical approach, advanced/metastatic melanoma still remains with a poor prognosis. Indeed, although enormous progress in the therapeutic treatment of human tumors has been made in recent years, patients affected by metastatic melanoma are still poorly affected by these clinical advances. Therefore, new valuable therapeutic approaches are urgently needed, to design and define effective treatments to consistently increase the overall survival rate of patients affected by this malignancy. In this review we summarize the main signaling pathways studied to kill human skin melanoma, and introduce the ferroptotic cell death as a new pathway to be explored to eradicate this tumor.